Natropalermoite, Na2SrAl4(PO4)4(OH)4, a new mineral isostructural with palermoite, from the Palermo No. 1 mine, Groton, New Hampshire, USA. (1st August 2017) - Schumer, Benjamin; Yang, Hexiong; Downs, Robert
Natropalermoite, ideally Na2SrAl4(PO4)4(OH)4, the Na-analogue of palermoite, is a new mineral from the Palermo No. 1 mine, Groton, New Hampshire, USA. Associated minerals are palermoite, eosphorite and quartz. Natropalermoite crystals are prismatic with striations parallel to the direction of elongation (the a axis) up to 200 μm × 50 μm × 45 μm in size. The mineral is colourless, transparent with a white streak and vitreous lustre and is visually indistinguishable from palermoite. It is brittle with subconchoidal fracture and has a Mohs hardness of 5.5. Cleavage is perfect on {001}, fair on {100} and no parting was observed. The calculated density is 3.502 g cm–3. Natropalermoite is biaxial (–), α = 1.624(1), β = 1.641(1), γ = 1.643(1) (589 nm), 2Vmeas = 43(4)°, 2Vcalc = 38°. An electron microprobe analysis yielded an empirical formula (based on 20 O apfu) of (Na1.69Li0.31)∑2.00(Sr0.95Mg0.04Ca0.02Ba0.01)∑1.02(Al3.82Mn0.03Fe0.03)∑3.88(P1.01O4)4(OH)4. Natropalermoite is orthorhombic, space group Imcb, a = 11.4849(6), b = 16.2490(7), c = 7.2927(4) Å, V = 1360.95(17) Å3, Z = 4. Natropalermoite is isotypic with palermoite, but substitution of the larger Na for Li results in substantial increase of the b cell parameter. Four of the seven Na–O distances are longer than their equivalents in palermoite, resulting in a more regular 7-fold coordination polyhedron about Na. The eight strongest peaks in the calculated X-ray powder diffraction are [dcalc(Å), Irel%, (hkl)]: [3.128, 100, (321)], [4.907, 68, (121)], [3.327, 48, (022)], [4.689, 45, (220)], [3.078, 45, (202)], [2.453, 38, (242)], [2.636, 35, (411)], [2.174, 35, (422)].